Exploring poems to promote language learners’ creative writing - Yasemin (Procedia - Social and Behavioral Sciences, 2023)
This article describes how poems can effectively be used to foster EFL/ESL students’ creative writing. The paper starts with discussing the meaning of creativity, and the importance of creativity within the language learning process. Then, it proceeds to demonstrate how students’ creative writing can be fostered by composing English poems. A three-stage writing using model advocated by Bouman (1983) is employed to promote students’ creative writing skills. Creativity in writing isb assessed using abrubric specifically designed for this study. Sample writings of poems produced by learners are included to illustrate how the use of model poems, which is used as a source of input, can facilitate creative writing.